CC and C chemokine expression in pulmonary sarcoidosis - Petrek, M; Kolek, V; Szotkowská, J; du Bois, R M (The European respiratory journal, 2002)
The chemokines RANTES (regulated on activation, T-cell expressed and secreted; CC chemokine ligand (CCL)-5) and monocyte inflammatory protein (MIP)-1alpha (CCL-3) have been implicated in the development of alveolitis in pulmonary sarcoidosis. The novel C chemokine single cysteine motif (SCM)-1alpha (XCL-1) and the CC chemokine monocyte chemoattractant protein (MCP)-1 (CCL-2) are also mononuclear-cell attractants and represent alternative candidate mediators of alveolitis. Therefore, the expression of MCP-1 and SCM-1alpha was investigated together with the expression of RANTES and MIP-1alpha in bronchoalveolar lavage fluid (BALF) from control subjects and patients with sarcoidosis. The relationship between chemokine expression and sarcoidosis clinical course was also explored. Messenger ribonucleic acid (mRNA) expression for all four chemokines was determined by semiquantitative reverse transcriptase-polymerase chain reaction of RNA extracted from unseparated bronchoalveolar cells (17 patients, 12 controls). RANTES, MIP-1alpha and MCP-1 proteins were measured by enzyme-linked immunosorbent assay of unconcentrated BALF (60 patients, 17 controls). MCP-1, and namely RANTES and SCM-1alpha mRNA expression was upregulated in sarcoidosis, particularly in patients with more advanced disease. RANTES, and namely MCP-1 concentrations were elevated in BALF samples obtained from patients; MCP-1 levels were most increased in patients with chest radiographic stage 2 disease and also in patients with persistent and recurrent disease. In conclusion, chemokines monocyte chemotactive protein-1 and single cysteine motif-1alpha are, in addition to RANTES, associated with the development of alveolitis in sarcoidosis and their expression parallels the disease course.
Keywords: exprese genu; Humans; messenger RNA; Gene Expression; Sarcoidosis, Pulmonary; chemokiny CC; Female; dospělí; polymerázová řetězová reakce s reverzní transkripcí; ELISA; Bronchoalveolar Lavage Fluid; Chemokines, C; lidé; Reverse Transcriptase Polymerase Chain Reaction; chemokin CCL2; Enzyme-Linked Immunosorbent Assay; Macrophage Inflammatory Proteins; Adult; Chemokines, CC; RNA, Messenger; chemokin CCL4; Chemokine CCL5; ženské pohlaví; Male; bronchoalveolární lavážní tekutina; Chemokine CCL2; plicní sarkoidóza; Chemokine CCL4; chemokin CCL5; chemokin CCL3; chemokiny C; makrofágové zánětlivé proteiny; mužské pohlaví; Chemokine CCL3